KOMPETENSI GURU DALAM MENGEMBANGKAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) DENGAN TUNTUTAN ABAD 21 DI SD NEGERI 24 BANDA ACEH - Liana, Nurul -; Z, Soedirman; Fitriani, Suci (Elementary Education Research, 2023)
Facing the 21st century is a challenge for teachers to make changes to the learning paradigm where the learning process is student-centered. Increasing creativity, character, and literacy as well as the use of technology is a challenge for teachers how to design lesson plans that develop 4C, PPK, Literacy, ICT and HOTS skills in the lesson plan components. Teacher competence plays an important role in designing and developing lesson plans to create a pleasant learning atmosphere. However, teachers' understanding in designing and developing 21st century components in lesson plans is not maximized. Thus the researcher is interested in seeing the competence of the teacher in designing the lesson plans that have been made. This study aims to describe how teacher competence is in developing lesson plans with the demands of the 21st century. This research method is a qualitative method with a descriptive approach. The subjects in this study were class III and class VI teachers. Obtaining data using observation data collection techniques, interviews, and documentation. Data analysis techniques using data reduction analysis techniques, data presentation, and conclusions. Based on the results of the research, SD Negeri 24 Banda Aceh teachers had difficulties in designing learning materials that were interrelated. Learning activities are not in accordance with the selection of models and methods. The use of technology-based learning media is still difficult due to limited facilities. However, based on the results of the analysis of teacher competency data, 80.95% for class III and 85.71% for class VI. The results show that teacher competence is included in the capable category. This is based on the range of values between 69% -100%. It can be concluded that teachers are capable of developing learning implementation plans with the demands of the 21st century at SD Negeri 24 Banda Aceh.